The prevalence and associated predictors for Bethesda III–VI for reporting thyroid cytopathology in Royal Commission Hospital, Kingdom of Saudi Arabia. (September 2022) - Alyousif, Hussain; Adam, Ishag; Alamin, Naser A.; Sid Ahmed, Mona A.; Al Saeed, Ayat; Hassoni, Abdulmuhsen Hussein; Musa, Imad R.
Background: Thyroid cancer is increasing globally and is currently the most prevalent endocrine malignancy. Recent data show an increase in the incidence of thyroid cancer in the Kingdom of Saudi Arabia (KSA). Thyroid ultrasound and fine-needle aspiration cytology (FNAC) are the cornerstones in managing thyroid nodules. We conducted this study to evaluate the prevalence and the associated predictors for thyroid nodule Bethesda III–VI in eastern KSA. Methods: A retrospective study was conducted between January 2015 and 31 August 2021. The participants were recruited patients who received a thyroid ultrasound and ultrasound-guided thyroid FNAC, using the thyroid imaging reporting and data system (TI-RADS) and the Bethesda Classification, respectively. Result: Three hundred and ten patients who underwent thyroid FNAC were enrolled in the study. The median (interquartile, IQR) age was 47.0 (20.0) years, and 266 (85.8%) of them were females. The median (IQR) body mass index was 30.2 (7.6) kg/m 2 . Out of these participants, 64.8% were euthyroid, 27.4% had hypothyroidism and 7.7% had hyperthyroidism. The ACR TI-RADS-3, 4 and 5 were 51.3%, 46.1% and 2.6%, respectively. The Bethesda outcome of thyroid FNAC I–VI was 5.2%, 63.9%, 15.5%, 5.8%, 3.5% and 6.1%, respectively. The risk for malignancy (Bethesda III–VI) was documented in 31.0% and atypia of undetermined significance was most prevalent (15.5%). A higher ACR TI-RADS score was associated with a higher risk of malignancy: ACR TI-RADS-3 (20.8%), ACR TI-RADS-4 (39.2%) and ACR TI-RADS-5 (87.5%). In a multivariate analysis, only the ACR TI-RADS score was significantly associated with the outcome of thyroid FNAC: ACR TI-RADS-4 [OR = 2.59 (95% CI = 1.54–4.36)] and ACR TI-RADS-5 [OR = 29.03 (95% CI = 3.44–245.07)]. Conclusion: There was a high prevalence of Bethesda III–VI and atypia of undetermined significance was most prevalent. A thyroid ultrasound report for TI-RADS was significantly associated with the outcome of thyroid FNAC and is a reliable tool in the absence of molecular testing for thyroid cancer.